EXPERIMENTAL DETERMINATIONAND SIMPLIFIEDMODELING APPROACHESTHERMO-PHYSICAL PROPERTIES OF WOOD BORASSUS (PALMYRA PALM) - AHOUANNOU, CLÉMENT; VODOUNNOU, Edmond; AGOUA, E. EUSÈBE; SANYA, EMILE ADJIBADÉ; GBAGUIDI, S. VICTOR; JANNOT, Yves; VIANOU, COKOU ANTOINE (My University, 2014)
This paper presents research results of an experimental study on the thermal properties of wood aethiopum Borassus (Palmyra palm) operated in Benin. Properties such as density, specific heat capacity and thermal diffusivity were measured and were used to estimate the conductivity and thermal effusivity of wood species. The so-called steady state method is used to measure the diffusivity (a); while the values of the thermal conductivity (λ) and thermal effusivity (E) are deducted in three directions from theoretical correlations. Test results by the method of the steady state gave the respective mean values of the thermal diffusivity according to the axes (o, x), (o, y) and (o, z) : 2.54*10-7 m2/s , 1.97*10-7 m2/s 1.80*10-7 m2/s. As for conductivity and thermal effusivity, the calculated values are respectively 0.34 W/m.K, and 682.01 J.m2.K-1.s-1/2 ; 0.27 W/m.K and 600.63 J.m2.K-1.s-1/2 ; 0.24 W/m.K and 557.95 J.m2.K-1.s-1/2. Thermal or mechanical and physical characteristics of the wood species studied and the sustainability of Borassus material in traditional constructions possible to envisage its use as reinforcement in concrete.
Keywords: Borassus Aethiopum (palm rônier); transfer of heat; physical properties; conductivity; diffusivity